2020
DOI: 10.1111/jai.14117
|View full text |Cite
|
Sign up to set email alerts
|

Migration and distribution of adult hatchery reared Yangtze sturgeons ( Acipenser dabryanus ) after releasing in the upper Yangtze River and its implications for stock enhancement

Abstract: The Yangtze sturgeon (Acipenser dabryanus) is a most important aquatic animal at the national level. Influenced by human activities such as dam constructions and overfishing, its natural population in the wild has almost disappeared. Since 2000, its natural reproduction has not been detected. In May 2018, in the Yibin reaches of the upper Yangtze River, 40 adult hatchery reared Yangtze sturgeons with their gonads at or above stage III, body length ranging from 92 to 146 cm were ultrasonically labeled and relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…By tracking and monitoring mature sturgeons released into the wild, it was found that they rarely migrated a long distance downstream, unlike the migration of young sturgeons following release [13]. Furthermore, mature sturgeons were predominantly distributed in the Jinsha River below Xiangjiaba Dam and the mainstream of the upper reaches of the Yangtze River [15]. The distribution of released juvenile fish covered approximately 500 km from Yibin to Fuling, and the primary gathering area was from Yibin to Hejiang River (Figure 3).…”
Section: Key Habitat Functionalitymentioning
confidence: 99%
“…By tracking and monitoring mature sturgeons released into the wild, it was found that they rarely migrated a long distance downstream, unlike the migration of young sturgeons following release [13]. Furthermore, mature sturgeons were predominantly distributed in the Jinsha River below Xiangjiaba Dam and the mainstream of the upper reaches of the Yangtze River [15]. The distribution of released juvenile fish covered approximately 500 km from Yibin to Fuling, and the primary gathering area was from Yibin to Hejiang River (Figure 3).…”
Section: Key Habitat Functionalitymentioning
confidence: 99%